Development of tubular cardiovascular phantom system for pulse transit time simulation - Wan Zaki, Wan Suhaimizan; Correia, Ricardo; Korposh, Serhiy; Hayes-Gill, Barrie R.; P. Morgan, Stephen (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
This paper presents on the development of a tubular cardiovascular phantom system to simulate pulse transit time (PTT). The PTT defined as the delay time between two pulses in one cardiac cycle has been shown to be promising method for cuffless continuous blood pressure (BP) measurement. However most of the PTT measurement was performed on human subjects, thus giving a difficulty in validating sensor performance due to variability of BP. Therefore, a cardiovascular phantom system was proposed for simulate the PTT measurement. An electronic controlled module was developed to control pump operation for pulse generation. Plastic optical fibre (POF) sensors were used to measure the pulse signal on the flexible tube and the results were compared with an in-line pressure sensor. In this experiment, the delay time between two pulses were calculated offline using Matlab software and correlated with pulse pressure. The result demonstrate that the pulse delay time recorded by both sensors decreased with increase of pulse rate and pulse pressure. These results on the phantom study showed similar pattern to the human model, thus indicating that the system is able to simulate PTT for sensor validation purposes.